Cost-effectiveness of immune checkpoint inhibitors and chemotherapy in triple-negative breast cancer: a scoping review - Venanti, Bernadeta Setyo; Rizky Danang Susetyo; Hilmy Irsyadi Hanif; Tri Murti Andayani; Zullies Ikawati (Indonesian Journal of Pharmacology and Therapy, 2025)
Triple-negative breast cancer (TNBC) is an aggressive malignancy associated with poor clinical outcomes and substantial economic burden. Standard chemotherapy treatment offers limited survival benefits, whereas immune checkpoint inhibitors (ICIs) have broadened therapeutic options. This review evaluates the cost-effectiveness of ICIs compared to conventional chemotherapy in TNBC and aims to identify which ICI provides the most favorable economic value. Using the PICO framework, which focuses on TNBC patients receiving chemotherapy as intervention and ICIs as comparators. The primary outcomes include incremental cost-effectiveness ratio (ICER), quality-adjusted life years (QALYs), and/or life years gained (LYG). Thearticles were selected based on the PRISMA strategy. A comprehensive selection of articles published from January 2020 to December 2024 was analyzed from PubMed, Google Scholar, Cochrane, and Scopus. TNBC commonly shows high tumor T-cell infiltration and Programmed Death Ligand-1 (PD-L1) expression, making ICIs such as atezolizumab and pembrolizumab viable treatment options. Atezolizumab improvedprogression-free survival (PFS) but was not found to be cost-effective in Singapore or the U.S. Pembrolizumab, however, significantly improved event-free survival (EFS) and demonstrated cost-effective across multiple countries, including Egypt, the United States of America (USA), and Switzerland. Sacituzumab govitecan, despitesurvival benefits in metastatic TNBC, showed high ICERs and poor cost-effectiveness. Pembrolizumab combined with chemotherapy appears to be more cost-effective than atezolizumab for PD-L1-positive TNBC patients. Meanwhile, sacituzumab govitecan has not been demonstrated to be cost-effective.